EFEKTIVITAS BERCERITA MENGGUNAKAN FINGER PUPPETS (APE) TERHADAP KEPATUHAN MENGGOSOK GIGI PADA ANAK USIA PRA SEKOLAH DI TK BUNAYYA IV MEDAN TAHUN 2015 - Afniwati Afniwati (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
The results of survey of household health (SKRT) DEPKS in 2012 indicates that dental caries is a high prevalence for 30% of children. The children with the dental caries are 18% while 12% of the children did not care their teeth. The result of observation at TK. Bunayy IV Medan it indicates that 25 students have dental caries caused by the poor of dental health care for the students.This research aims to study the compliance of the students of TK Bunayya IV Medan in 2015 by Pre-Posttest Design. The population and sample in this research is students of TK Bunayya IV Medan for 68 students by total sampling method.The result of research before storytelling using finger puppets, the number of student who did not comply to brush the teeth is 43 respondent (63.2%) and after theintervention, the compliance in teeth brushing is 61 respondent (89.7%). The result of statistical test obtain the significant result to the increasing of compliance in teeth brushing with P = 0.000.It is suggested to the health staff to use the storytelling method using finger puppet to the children with dental caries to increase their compliance.